Effects of Vitamin-Mineral Supplementation on Cardiac Marker and Radical Scavenging Enzymes, and MDA Levels in Young Swimmers - Cavas, L.; Tarhan, L. (International Journal of Sport Nutrition and Exercise Metabolism, 2004)
The relationship among the enzyme activities of cardiac markers, the antioxidant defense system, and erythrocyte membrane malonyldialdehyde (MDA) levels related to vitamin-mineral supplementation in swim exercise was investigated. Swimmers aged 11-13 years were divided into 2 separate groups as control and vitamin-mineral supplemented. Swimmers participated in a monthly swimming program (4 times/wk) and swam approximately 2-2.5 km/d. Cardiac markers such as creatine kinase (CK), creatine kinase-MB (CK-MB), glutamic oxaloacetic transaminase [GOT (AST)], lactate dehydrogenase (LDH), and anti-oxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) activities in post-training samples were found to be significantly (p < .05) higher than in pre-training samples. Except for GOT (AST), the activity increases in CK, CK-MB, and LDH in female and male supplemented groups were significantly (p < .05) lower than those of control groups during the 1-month period of swim training. Antioxidant enzyme activity increases in the male vitamin-mineral group were significantly (p < .05) higher when compared with the other groups. Post-training MDA levels were significantly (p < .001) higher than pre-training MDA levels in the control groups, whereas no significant (p > .05) differences were found between the vitamin-mineral supplemented groups. Vitamin-mineral supplementation was found to attenuate cardiac and muscle damage markers while also enhancing antioxidant levels and reducing membrane LPO levels in response to 1 month of swim training.